Fibrocytes in the fibrotic lung: altered phenotype detected by flow cytometry - Reese, Charles; Lee, Rebecca; Bonner, Michael; Perry, Beth; Heywood, Jonathan; Silver, Richard M.; Tourkina, Elena; Visconti, Richard P.; Hoffman, Stanley (Frontiers in Pharmacology, 2014)
Fibrocytes are bone marrow hematopoietic-derived cells that also express a mesenchymal cell marker (commonly collagen I) and participate in fibrotic diseases of multiple organs. Given their origin, they or their precursors must be circulating cells before recruitment into target tissues. While most previous studies focused on circulating fibrocytes, here we focus on the fibrocyte phenotype in fibrotic tissue. The study's relevance to human disease is heightened by use of a model in which bleomycin is delivered systemically, recapitulating several features of human scleroderma including multi-organ fibrosis not observed when bleomycin is delivered directly into the lungs. Using flow cytometry, we find in the fibrotic lung a large population of CD45high fibrocytes (called Region I) rarely found in vehicle-treated control mice. A second population of CD45+ fibrocytes (called Region II) is observed in both control and fibrotic lung. The level of CD45 in circulating fibrocytes is far lower than in either Region I or II lung fibrocytes. The chemokine receptors CXCR4 and CCR5 are expressed at higher levels in Region I than in Region II and are present at very low levels in all other lung cells including CD45+/collagen I- leucocytes. The collagen chaperone HSP47 is present at similar high levels in both Regions I and II, but at a higher level in fibrotic lung than in control lung. There is also a major population of HSP47high/CD45- cells in fibrotic lung not present in control lung. CD44 is present at higher levels in Region I than in Region II and at much lower levels in all other cells including CD45+/collagen I- leucocytes. When lung fibrosis is inhibited by restoring caveolin-1 activity using a caveolin-1 scaffolding domain peptide (CSD), a strong correlation is observed between fibrocyte number and fibrosis score. In summary, the distinctive phenotype of fibrotic lung fibrocytes suggests that fibrocyte differentiation occurs primarily within the target organ.